Intrathecal baclofen for long-term treatment of spasticity: a multi-centre study. Issue 8 (August 1989) - Ochs, G; Struppler, A; Meyerson, B A; Linderoth, B; Gybels, J; Gardner, B P; Teddy, P; Jamous, A; Weinmann, P
Abstract : Twenty eight patients with severe, intractable spasticity have been treated by chronic intrathecal administration of baclofen. An implantable programmable drug-administration-device (DAD) was used with a permanent intrathecal catheter. Infusion of 50 to 800 micrograms/day of baclofen completely abolished spasticity. Follow-up was up to two years. Therapeutic effect was documented by clinical assessment of tone, spasms and reflexes and by electrophysiological recordings of mono- and polysynaptic reflex activity. Complications and untoward side-effects of the procedure were few. This procedure is recommended for spasticity of spinal origin refractory to physiotherapy and oral medication. It is a preferable alternative to ablative surgical intervention.